2016
DOI: 10.1007/s11010-016-2790-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of endothelial nitric oxide synthase (eNOS) gene G894T polymorphism with hypertension risk and complications

Abstract: This study evaluated the association of NOS3 polymorphisms with hypertension risk and complications. eNOS (G894T) SNP was performed by RT-PCR on 70 hypertensive patients (25 were hypertensive, 25 were hypertensive with CAD, and 20 were diabetic with hypertension) and 30 age- and gender-matched individuals. Lipid and glucose profile were assessed by standard colorimetric assay. Our results revealed that combination of (GT + TT) genotype and T allele significantly increases the risk of hypertension (OR = 3.86 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…However, this effect was not observed in the arteries from Wistar rats in the present study, a result in line with that of Zhang et al ( 2004 ), implying that the effect of Rhy is to restore the impaired eNOS activity but not to increase the activity of normally functioning eNOS. As abnormal eNOS occurs commonly among patients with hypertension (Cengiz et al, 2015 ; ALrefai et al, 2016 ), these findings highlight that the patients with endothelial dysfunction might benefit from the endothelium-protective potential of Rhy.…”
Section: Discussionmentioning
confidence: 79%
“…However, this effect was not observed in the arteries from Wistar rats in the present study, a result in line with that of Zhang et al ( 2004 ), implying that the effect of Rhy is to restore the impaired eNOS activity but not to increase the activity of normally functioning eNOS. As abnormal eNOS occurs commonly among patients with hypertension (Cengiz et al, 2015 ; ALrefai et al, 2016 ), these findings highlight that the patients with endothelial dysfunction might benefit from the endothelium-protective potential of Rhy.…”
Section: Discussionmentioning
confidence: 79%
“…Also, several studies showed a strong association between 894 G > T polymorphism of NOS3 gene and hypertension [18,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…ТТ-генотип полиморфизма гена NOS3 был связан с риском атеросклеро- [35]. TT и GT генотипы были ассоциированы с риском ИБС [36,37] и АГ [38]. Результаты нашего исследования согласуются с исследованием Campedelli с соавт., где наличие GG-генотипа повышало предрасположенность к атеросклерозу [39].…”
Section: результаты и обсуждениеunclassified